2013
DOI: 10.1353/pla.2013.0038
|View full text |Cite
|
Sign up to set email alerts
|

Publish or Practice? An Examination of Librarians’ Contributions to Research

Abstract: This article examines authorship of LIS literature in the context of practitioner and nonpractitioner production of published research. For this study, 4,827 peer-reviewed articles from twenty LIS journals published between 1956 and 2011 were examined to determine the percentage of articles written by practitioners. The study identified a decrease in the proportion of articles authored by practitioners between 2006 and 2011. Topic analysis of articles revealed subtle yet distinct differences in research subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 34 publications
2
14
1
Order By: Relevance
“…These six journal types are generally consistent with those identified in previous research (Finlay et al., ; Ni et al., ; Ni, Sugimoto, & Jiang, ). They represent all three of the LIS research perspectives identified by Milojević, Sugimoto, Yan, and Ding ()—libraries, information, and scientometrics—and are consistent with the subfields described by Tuomaala, Järvelin, and Vakkari ().…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…These six journal types are generally consistent with those identified in previous research (Finlay et al., ; Ni et al., ; Ni, Sugimoto, & Jiang, ). They represent all three of the LIS research perspectives identified by Milojević, Sugimoto, Yan, and Ding ()—libraries, information, and scientometrics—and are consistent with the subfields described by Tuomaala, Järvelin, and Vakkari ().…”
Section: Resultssupporting
confidence: 90%
“…Finlay et al. () and Stewart (, ) are the only authors to have adopted this approach in recent years. Access to each article was obtained through full‐text databases, online subscriptions, and print subscriptions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While journals such as the American Journal of Public Health [2] outline individual author roles in the publication, these details are not required by all International Committee of Medical Journal Editors journals [3]. Several studies and reports discuss research performed by librarians and the barriers or support mechanisms that influence librarian participa tion in research [4][5][6][7][8][9][10][11], Many factors contribute to readiness to collaborate on research: personal and motivational factors, job duties, structural support, and skill-based preparation. In 2010, Luo found only 61% of 49 accredited library programs require a research * Based on a paper presented at MLA '13, the 113th Annual Meeting of the Medical Library Association; Boston, MA; May 7, 2013. This article has been approved for the Medical Library Association's Independent Reading Program < http://www.mlanet .org/education/irp/>.…”
Section: Introductionmentioning
confidence: 99%